Social Media Survey and Web Posting Assessment of the COVID-19 Response in China: Health Worker Attitudes Toward Preparedness and Personal Protective Equipment Shortages. (31st August 2020) - Huang, Dayong; Shu, Wen; Li, Menglong; Ma, Juntao; Li, Ziang; Gong, JiaJian; Khattab, Nourhan M; Vermund, Sten H; Hu, Yifei
Abstract: Background: Understanding health worker awareness, attitudes, and self-confidence in the workplace can inform local and global responses toward emerging infectious threats, like the coronavirus disease 2019 (COVID-19) pandemic. Availability of accessible personal protective equipment (PPE) is vital to effective care and prevention. Methods: We conducted a cross-sectional survey from February 24 to 28, 2020, to assess COVID-19 preparedness among health workers. In addition, we assessed trends from search engine web crawling and text-mining data trending over the Sina Weibo platform from January 1 to March 3, 2020. Data were abstracted on Chinese outbreak preparedness. Results: In the survey, we engaged 6350 persons, of whom 1065 agreed to participate, and after an eligibility logic check, 1052 participated (16.6%). We accessed 412 internet posts as to PPE availability. Health workers who were satisfied with current preparedness to address COVID-19 were more likely to be female, to obtain knowledge about the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak from government organizations, and to consider their hospital prepared for outbreak management. Health workers with more confidence in their abilities to respond were those with more faith in their institution's response capacities. Elements of readiness included having airborne infection isolation rooms, visitor control procedures, and training in precautions and PPE use. Both survey and web post assessments suggested that health workers in need were unable to reliably obtain PPE. Conclusions: Health workers' self-confidence depends on perceived institutional readiness. Failure to maintain available PPE inventory for emerging infectious diseases preparedness suggests a failure to learn key lessons from the 2003–2004 SARS outbreak in China.